You are never too old for a congenital disease! - Mukul Khanna; Saro Sarkisian; Phu Tran; Ibrahim I. Ghobrial (Greater Baltimore Medical Center, 2013)
Congenital diseases are sometimes overlooked by physicians because of their rarity or because of late onset of symptoms, which may delay treatment plans. This is illustrated in our patient who presented with dysphagia along with chest pain and who was found to have a congenital vascular anomaly, detected in her fifth decade of life.